Identification and Screening of Enzymatic Activity of Degrading Fungi Microplastics in Three Final Processing Sites (TPA) in the Province Lampung - Oktaviyani, Sari; Kamelia, Marlina; Ulmillah, Aulia (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
One of the main causes of problems in the Final Processing Site (TPA) of Lampung Province is the increasing pile of plastic waste produced by human activities. This can be a source of microplastic pollution and is dangerous if it settles in the body of organisms. Fungi can be an alternative to help the natural biodegradation process reduce microplastic pollution in the soil ecosystem. This study aims to identify and characterize fungal isolates that can degrade microplastics in the Final Processing Site (TPA) of Lampung Province. The sampling method was purposive sampling. The growing colonies were identified by observing the clear zone, then characterized morphologically. Data analysis using qualitative descriptive methods and measuring the clear zone index. This study successfully identified 13 fungal isolates that showed clear zone areas. Four isolates (Ba1.2, Ba2.5, Bu3.4, Ka2.3) could degrade three types of microplastics. The highest clear zone: Bu3.4 for PET (2,00 mm), Ka2.4 for PE (1,50 mm), and Ba2.3 and Ba2.5 for PP (1,25 mm). Identification and morphological characterization showed 8 isolates belonging to the genus Aspergillus, 3 isolates of Penicillium, 1 isolate of Fusarium, and 1 isolate of Sclerotium. Degradation occurs through hyphal adhesion and secretion of polymer-degrading enzymes.